Enhancing Athlete Performance with Mobile Health Applications: Benefits and Challenges - Wahyudi, Nanang Tri; Yunus, Moch (Tarqabin Nusantara Group, 2025)
Introduction:Mobile health applications have gained significant attention in recent years due to their ability to enhance athletic performance, prevent injuries, and support overall health management. By integrating advanced technologies, these applications provide athletes with personalized exercise plans, real-time monitoring of physiological and psychoemotional indicators, and immediate feedback. Method:This study employed a systematic literature review (SLR) using the PRISMA framework to identify, screen, and synthesize peer-reviewed studies published between 2013 and 2023. Databases including PubMed, Scopus, and Web of Science were searched using terms such as